On adsorption-induced denaturation of folded proteins. - Fernández, Ariel; Ramsden, Jeremy J. (Jointly by, Collegium Basilea (Institute of Advanced Study) and Association of Modern Scientific Investigation., 2001)
In the absence of intramolecular long range interactions, the extended local conformation of a peptide chain is entropically favoured over compact ones, since the area of the Ramachandran basin of attraction is larger for the extended local conformation than for any other. In consequence, a random coil is predominantly in the extended conformation. Under refolding conditions, the high entropic content of the random coil is countered by the enthalpy loss associated with intramolecular contact formation (“hydrophobic collapse”) and compactification of the chain. At an appropriate protein-binding surface, however, the enthalpy loss can be achieved at minimal cost of conformational entropy, since contacts can be formed between the protein and the surface and hence do not require compactification of the protein chain. This saving in entropic cost is a central concept for understanding the surface-induced denaturation of folded proteins.
Keywords: adsorption; conformation; denaturation; folding; protein